When the written and visual texts collide: photographic images and acts of memory in Zimbabwean autobiography - Ngoshi, Hazel T. (Taylor & Francis (Routledge), 2016)
Studies focusing on the inclusion of visual/photographic images in autobiographical narratives have recently gained currency. This article is based on the notion that photography is a mode of representation and a technology of memory; and it will critique the strategic deployment of photographic images in autobiographies of Zimbabwean politicians. The article explores the dynamics of how photographic images render remembering and self-construction possible in Joshua Nkomo’s The story of my life, Fay Chung’s Re-living memories of the second chimurenga and Edgar Tekere’s A lifetime of struggle. When visual and written texts collide, it becomes an act of memory and this visual-print-text paradigm in autobiographies is a site where official national memory and private memory can be interrogated. Images serve to negotiate the conflict between the autobiographical subject, national memory and the ideology of representation. This article posits that, when photographic images are included in autobiographies, they become implicated in the politics of remembering, and in how the self and national memories are perceived.